Guide to grammar & writing dedicated to the memory of Dr. Charles Darling [electronic resource] - Darling, Charles Dr (Capital Community College Foundation, 2004)
Quoted from the homepage: The Guide to Grammar and Writing is sponsored by the Capital Community College Foundation, a nonprofit 501 c-3 organization that supports scholarships, faculty development, and curriculum innovation. If you feel we have provided something of value and wish to show your appreciation, you can assist the College and its students with a tax-deductible contribution.